Pengaruh Citra Bank dan Promosi Undian Ghendis Manis Terhadap Keputusan Petani Tebu Menabung di Bank: Studi Kasus Bank Rakyat Indonesia Kantor Cabang Lumajang - Umar Makruf; Hesti Budiwati (Jurnal Ilmu Manajemen Advantage, 2017)
The study aims to knowed influence of bank image and promotion on gamling gendis manis to farming dicision to saving in Lumajang Branch office of BRI. Either partially of simultaneously. This research is quantitative research to find the associative relationship that are causal or the research to ask the question the relations between two or more variable and cause effect relation. The study aims to find evidence of the influence of bank image and promotion on saving decisions of Lumajang Barnch Office of Bank Rakyat Indonesia either partially or simultaneously. This study tested the hypothesis that there is a bank image effect on the saving decisions, there is promotion on saing decisions, and there is the influence of bank image and promotion to work simultaneously on the performance of employees at the National Narcotics Agency office Lumajang. The study, of 45 respondents using multiple linear regression analysis is the bank image there is an influence on saving decisions, there is work promotion on saving decisions, and there is the influence of bank image and promotion to work simultaneously on the decisions of saving at the Lumajang Barnch Office of Bank Rakyat Indonesia. Simple linear regression function generated is Y= 4,096 + 0,345X1 + 0,183X2. The coefficient of determination showed that 53,5 of saving decisions can be explained by the bank image and promotion t, while the remaining 46,5% of saving decisions is influenced by other variables not examined in this study.